Sosialisasi Penguatan Pedagogical Content Knowledge (PCK) Berbasis Teknologi bagi Guru Sekolah Dasar dalam Mewujudkan Pembelajaran Berdampak - Sundahry sundahry; Yogi Irdes Putra; Muhammad Ripal (GERAKAN EDUKASI DAN MASYARAKAT NUSANTARA, 2026)
Abstract The competence of elementary school teachers in designing and implementing quality learning is a determining factor in the success of education. One of the fundamental competency frameworks that is still not widely understood is Pedagogical Content Knowledge (PCK), which refers to teachers’ ability to integrate mastery of subject matter with appropriate pedagogical strategies. Based on preliminary observations of elementary school teachers in Bungo Regency, it was found that many teachers still did not fully understand the concept of PCK and had not been able to integrate it with the use of digital technology. As a result, the learning process had not been able to provide meaningful and sustainable impacts on students. This community service activity was carried out through a structured socialization program consisting of five main stages: (1) preparation and needs analysis through surveys and Focus Group Discussions (FGD), (2) socialization of technology based PCK concepts through interactive training methods, (3) workshops on developing impactful learning through a project-based learning approach, (4) implementation and trial of learning designs in the classroom, and (5) evaluation and the establishment of a digital teacher learning community. The activity took place from February 23 to March 12, 2026, involving elementary school teachers in Bungo Regency as participants. The results of the socialization program showed that participating teachers experienced significant improvement in their understanding of PCK concepts and their ability to integrate them with digital technology. A total of 92% of participants successfully developed at least one impactful learning tool based on digital PCK according to the subjects they taught. The establishment of a digital teacher learning community serves as a guarantee for the sustainability of the program, enabling the continuous and independent development of teachers’ PCK competencies. Keywords: Socialization; PCK; Technology; Impactful Learning; Elementary School Teachers.